Corrosion protection of unbonded tendons FIP recommendations. (Thomas Telford, 1986)
Unbonded tendons are popular in certain types of structure for reasons of economy and speed of construction. The FIP Commission on Pre-stressing Steels and Systems accordingly appointed an ad hoc committee to investigate available knowledge and experience and to instigate research if necessary.